Dynamics and causes of changes in the condition of pine stands of different ages, managed by Khmelnytskyi Regional Department of Forestry and Hunting, during 1992–2018 - Усцький , І. М.; Жадан , І. В.; Михайліченко , О. А. (Forestry and Forest Melioration, 2022)
Introduction Khmelnytskyi region is located in the forest-steppe zone and the southern part of Western Polissia. On the lands of the region’s forestry enterprises, the protected area makes up 26% of the total forest area. In recent years, pine stands have been declining due to the invasion of the bark beetle – Ips acuminatus Gill. It, in turn, led to a significant increase in sanitary felling. Significant areas of pine stands covered by large-scale pathological processes, in particular, are also associated with the prohibition of forestry activities on a large area of protected territories. Considering the fact that in Khmelnytskyi region, pine stands occupy about one-third of the area covered by forest vegetation, it is relevant to define their mensuration characteristics and compare them to the resistant stands. The aim of the study was to determine the mensuration features of the pine stands in Khmelnytskyi region, in which pathological processes have been noted. Materials and Methods The pine stand distribution by origin and species composition was analysed in Khmelnytskyi region according to the forest management database as of 2010. Following the database information, changes in the pine stand condition were examined for 1992–2018 for each third year since 1994. We defined a degree of stand decline: the dieback of 5–10% is a low degree, 11–30% is a medium degree, and more than 30% is a severe decline. We generalized the collected information by means of special programmes, including specification of stand areas by age classes, the density of stocking, quality, and causes for their decline. Results Most of the pine stands were established in the 50s and 60s of the 20th century. Pure natural and artificial stands (70–100% of pine) made up 12–22% and 78–88% of the area, respectively. The proportion of planted stands is 72–92% among the pine stands of the 2nd–7th age classes. About 58% of all pine forests in Khmelnytskyi region are vulnerable to pathological processes. The share of the area of the pine stands where pathological processes were observed exceeds the percentage of the pine stands from the total forest area. As of 2009, the stand area with pathological processes increased sharply to 1.9 thousand hectares (medium degree, 4.4% of the area of all pine stands), and as of 2018, it reached more than 4 thousand hectares, respectively (severe decline degree, 9.1%). The main factors initiating the pine stand decline in Khmelnytskyi region were mostly climatic ones, such as droughts, sudden changes in temperature, high temperatures of the growing season, etc., which made from 21% (2006) to 86% (1997), diseases, 86% in 1994 and 66% in 2000, and a change of hydrological regime, 42.7% in 2006. The most extensive wind damage to the pine forests was registered in 2009, with 412 ha (4.2%) damaged. The largest snow damage of 430 ha (22% of total damaged stands for this period) and hail damage of 95 ha (4.9%) were recorded also this year. The most severe fire damage was observed in 2015 (1.8% of total damaged stands). The largest mortality was found in the stands of the 6th and 7th age classes, 29% and 24%, respectively. Conclusions Due to an outbreak of bark beetle (Ips acuminatus), the area of declining pine stands in Khmelnytskyi region increased in 2012, and in 2018 it reached almost 34 thousand ha. The background for the spread of apical bark beetle was the root rot and damage caused to pines by windbreaks and snowstorms (2009 – 0.8 thousand hectares) as well as fires (2000 – 1.5 thousand ha). The largest areas of the stands with pathological processes were observed in artificially created pure plantings of the 6th and 7th age classes. They made 64% of the area of all dying pine stands, of the 1st and higher site quality classes (93%), and with a relative density of stocking of 06–07. The data obtained show the need to reduce the maturity age for planted pine stands. 5 Figs., 3 Tables, 8 Refs.